Markers of the aerobic energy-delivery system as measures of post-match fatigue and recovery in soccer: A repeated measures design - Dillern, T. (Asian Journal of Sports Medicine, 2017)
Objectives: The aerobic energy-delivery system substantially contributes to energy consumption while playing soccer. Fatigue and recovery in soccer are hence closely related to this system`s efficiency, however research emphasizing this relationship is lacking. This study aimed at examining if it is possible to detect post-match fatigue and recovery in soccer players by exploring markers (e.g. oxygen consumption, heart rate, and blood lactate) of the aerobic energy-delivery system`s efficiency during a steady-state running test in the laboratory.